Safety and tolerability of Triumeq in amyotrophic lateral sclerosis: the Lighthouse trial. Issue 7 (2nd October 2019) - Gold, Julian; Rowe, Dominic B.; Kiernan, Matthew C.; Vucic, Steve; Mathers, Susan; van Eijk, Ruben P. A.; Nath, Avindra; Garcia Montojo, Marta; Norato, Gina; Santamaria, Ulisses A.; Rogers, Mary-Louise; Malaspina, Andrea; et al.
Abstract: Background : Neuroinflammation and human endogenous retroviruses (HERV) are thought to have a role in the pathophysiology of amyotrophic lateral sclerosis (ALS). Therapy directed against endogenous retroviruses has demonstrated positive effects during in vitro and biomarker studies. Consequently, the present study was undertaken to assess the safety and tolerability of long-term antiretroviral therapy (ART), Triumeq (abacavir, lamivudine, and dolutegravir) exposure in patients with ALS, and efficacy against biomarkers of disease progression. Methods : Patients were observed during a 10-week lead-in period before receiving Triumeq treatment for 24 weeks at four specialist ALS centers. The primary outcomes were safety and tolerability. Secondary outcomes included HERV-K expression levels, urinary p75 ECD levels, neurophysiological parameters, and clinical indicators. The ENCALS prediction model was applied to provide an estimate of the cohort survival. The trial was registered (NCT02868580). Findings : 40 patients with ALS received Triumeq and 35 (88%) completed treatment. There were no drug-related serious adverse events; one patient was withdrawn from the study due to a drug-associated increase in liver enzymes. A favorable response on HERV-K expression levels was observed, accompanied by a decline in ALSFRS-R progression rate of 21.8% (95% CI −4.8%–48.6%) and the amount of urinary p75 ECD measured. One patient died five months after stopping treatment, while five were expected to have died during the treatment period (interquartile range 2–8). Interpretation : Long-term Triumeq exposure was safe and well tolerated in this cohort. There was suggestive indication for a possible biological response in some pharmacodynamic and clinical biomarkers. A larger international phase 3 trial will be deployed to assess the effect of Triumeq on overall survival and disease progression. Funding: Funding was provided by the FightMND Foundation; MND Research Institute of Australia; MND Association, United Kingdom, and GSK. ViiV Healthcare provided the Triumeq.